The Wright 3 - Balliett, Blue, 1955-; Helquist, Brett (New York : Scholastic Press, 2006)
In the midst of a series of unexplained accidents and mysterious coincidences, sixth-graders Calder, Petra, and Tommy lead their classmates in an attempt to keep Frank Lloyd Wright's famous Robie House from being demolished.
Accelerated Reader AR
Keywords: Wright, Frank Lloyd, -- 1867-1959 -- Fiction; Robie House (Chicago, Ill.) -- Fiction